2015
DOI: 10.1016/j.soilbio.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of arbuscular mycorrhizal fungi associated with Robinia pseudoacacia in uncontaminated and heavy metal contaminated soils

Abstract: a b s t r a c tThe significance of arbuscular mycorrhizal fungi (AMF) in soil remediation has been widely recognized because of their ability to promote plant growth and increase phytoremediation efficiency in heavy metal (HM) polluted soils by improving plant nutrient absorption and by influencing the fate of the metals in the plant and soil. However, the symbiotic functions of AMF in remediation of polluted soils depend on plantefungusesoil combinations and are greatly influenced by environmental conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(73 citation statements)
references
References 84 publications
(89 reference statements)
10
62
0
1
Order By: Relevance
“…A variety of environmental factors could influence the AMF community structure, and among them, heavy metal contaminations (Pb, Zn, Cu and Cd) have been found to be important predictors (Yang et al, 2015). In addition to As, we also found that the Cd concentrations had a significant effect on the AMF community structure (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…A variety of environmental factors could influence the AMF community structure, and among them, heavy metal contaminations (Pb, Zn, Cu and Cd) have been found to be important predictors (Yang et al, 2015). In addition to As, we also found that the Cd concentrations had a significant effect on the AMF community structure (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Robinia pseudoacacia L. is a Pb-tolerant tree species (Yang et al, 2015c). The seeds were collected from Northwest A&F University (Yangling, Shaanxi Province, China) in 2013.…”
Section: Methodsmentioning
confidence: 99%
“…R. pseudoacacia is frequently found in HM contaminated areas and it may serve as an indicator of Pb pollution (Serbula et al, 2012). R. pseudoacacia plants are well grown and commonly colonized by AMF such as F. mosseae in the Qiandongshan lead–zinc polluted area (Yang et al, 2015b,c). Recent studies have shown that photosynthesis and antioxidant enzymes (e.g., superoxide dismutase and ascorbate peroxidases) in the leaves of R. pseudoacacia are enhanced by F. mosseae under Pb stress (Yang et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…The HM polluted area had the same soil type and was divided into polluted levels of light (S1, 33 • Figure S1), according to our previous investigation and the Chinese environmental quality standard (Grade II) for soils (GB 15618-1995) [27,[29][30][31]. In August 2012, four study plots (15 × 15 m) dominated by target tree species (R. pseudoacacia) were identified at each site for soil sampling.…”
Section: Study Area and Samplingmentioning
confidence: 99%